2016
DOI: 10.1177/1465750316648576
|View full text |Cite
|
Sign up to set email alerts
|

Preference for self-employment

Abstract: The preference for self-employment varies much between countries. The purpose of this study is to investigate the relationship between the preference for self-employment, new business start-up intentions and actual start-up efforts. This research is an application of the theory of planned behaviour. Data were collected using telephone interviews from a representative sample of Norwegian adults aged 18–64 years. The results support the theory, showing that the preference for self-employment, together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 42 publications
2
25
0
4
Order By: Relevance
“…A positive or favorable attitude towards a behavior, such as starting a business, is formed when perceived to have beneficial and desirable consequences. Specifically, the attitude towards entrepreneurship (AE) has shown a consistent and significant impact on EI in most of the research carried out in various contexts (Al-Jubari et al, 2018;Kautonen et al, 2015;Kolvereid, 2016). Considering the above, the following working hypothesis is proposed.…”
Section: Attitudementioning
confidence: 98%
See 1 more Smart Citation
“…A positive or favorable attitude towards a behavior, such as starting a business, is formed when perceived to have beneficial and desirable consequences. Specifically, the attitude towards entrepreneurship (AE) has shown a consistent and significant impact on EI in most of the research carried out in various contexts (Al-Jubari et al, 2018;Kautonen et al, 2015;Kolvereid, 2016). Considering the above, the following working hypothesis is proposed.…”
Section: Attitudementioning
confidence: 98%
“…In this sense, previous contributions show that the study of entrepreneurial intention (EI) is essential to understand the entrepreneurship process (Kautonen et al, 2015;Kolvereid, 2016). The closest predictor of the decision to become an entrepreneur is seen in EI; the intention can foreshadow behaviors (Fini et al, 2012), indicates how intensely you prepare and how much effort you are planning to commit to carrying out an entrepreneurial behavior (Bird, 1988;Carsrud and Brannback, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, entrepreneurial intentions have been extensively studied, but the distinction between entry modes to entrepreneurship is not always explicit. Parker and Praag (2012) pointed out aggregation problems that may ensue when different entry modes are combined, although Kolvereid (2016), for example, concluded that the intention to start a business/to become self-employed is largely interpreted by respondents in surveys as the same thing. Iakovleva and Kolvereid (2009) did find that, for Russian students at least, the intention to acquire a business is distinctly different from other entrepreneurial intentions.…”
Section: Theory Of Planned Behavior and Business Takeover Intentionsmentioning
confidence: 99%
“…Entrepreneurial intent has been studied in relation to parental selfemployment (Carr & Sequeira, 2007), social influences (Engle et al, 2011), personality (Prabhu et al, 2012) as well as other traits or treatments. Importantly, entrepreneurial intention has been found to be a predictor of subsequent self-employment adding validity to the concept (Kautonen et al, 2013;Kolvereid, 2016). Despite the proliferation of makerspaces across the country, scant research has studied how their use may shape entrepreneurial intent among young people.…”
Section: Literature Reviewmentioning
confidence: 99%